A whey/guar "preload" improves postprandial glycaemia and glycated haemoglobin levels in type 2 diabetes: A 12‐week, single‐blind, randomized, placebo‐controlled trial. Issue 4 (4th January 2019) - Watson, Linda E.; Phillips, Liza K.; Wu, Tongzhi; Bound, Michelle J.; Checklin, Helen L.; Grivell, Jacqueline; Jones, Karen L.; Clifton, Peter M.; Horowitz, Michael; Rayner, Christopher K.
Abstract : Aims: To evaluate the effects of 12 weeks of treatment with a whey/guar preload on gastric emptying, postprandial glycaemia and glycated haemoglobin (HbA1c) levels in people with type 2 diabetes (T2DM). Materials and methods: A total of 79 people with T2DM, managed on diet or metformin (HbA1c 49 ± 0.7 mmol/mol [6.6 ± 0.1%]), were randomized, in single‐blind fashion, to receive 150 mL flavoured preloads, containing either 17 g whey protein plus 5 g guar (n = 37) or flavoured placebo (n = 42), 15 minutes before two meals, each day for 12 weeks. Blood glucose and gastric emptying (breath test) were measured before and after a mashed potato meal at baseline (without preload), and after the preload at the beginning (week 1) and end (week 12) of treatment. HbA1c levels, energy intake, weight and body composition were also evaluated. Results: Gastric emptying was slower ( P < 0.01) and postprandial blood glucose levels lower ( P < 0.05) with the whey/guar preload compared to placebo preload, and the magnitude of reduction in glycaemia was related to the rate of gastric emptying at both week 1 (r = −0.54, P < 0.001) and week 12 (r = −0.54, P < 0.0001). At the end of treatment, there was a 1 mmol/mol [0.1%] reduction in HbA1c in the whey/guar group compared to the placebo group (49 ± 1.0 mmol/mol [6.6 ± 0.05%] vs. 50 ± 0.8 mmol/mol [6.7 ± 0.05%]; P < 0.05). There were no differences in energy intake, body weight, or lean or fat mass between the groups. Conclusions: In patients with well‐controlled T2DM, 12 weeks' treatment with a low‐dose whey/guar preload, taken twice daily before meals, had sustained effects of slowing gastric emptying and reducing postprandial blood glucose, which were associated with a modest reduction in HbA1c, without causing weight gain.